Causal model of quality of life in veterans of the nervous system in the aging process of Kermanshah province - Zh. Khaniabad; H. Amiri; K. Kakabraee (Afarand Scholarly Publishing Institute, 2020)
Aims: Identifying the prerequisites for the quality of life of neuropsychiatric veterans in a single model will lead to a better understanding of the quality of life of these individuals and, as a result, better provision of welfare services related to these prerequisites. Therefore, the aim of the present study was to design the causal model of prerequisites for the quality of life of neuropsychiatric veterans. Materials & Methods: This descriptive-correlational study of the structural equation model was conducted during 2017-2018 among 260 neuropsychiatric veterans covered by the Martyrs and Sacrifices Affairs Foundation of Kermanshah province. These people were selected by simple random sampling method and they completed research questionnaires including the short form questionnaire of the World Health Organization Quality of Life (WHOQOL-BREF), short form of marital satisfaction questionnaire, researcher-made questionnaire to assess the satisfaction of Martyr Foundation services, spiritual attitude questionnaire, multidimensional perceived social support scale, and healthy life style scale. Date were analyzed by SPSS 22 software and AMOS 24 software using descriptive and inferential statistics. Findings: The direct coefficients of satisfaction of services on quality of life (β=0.47), perceived social support on quality of life (β=0.44), and behaviors and positive attitudes toward health on quality of life (β= 0.16) were significant. The indirect path coefficients were also significant (p<0.01). Conclusion: Teaching spiritual attitudes and behaviors related to health, as well as increasing the services of the Martyrs Foundation, can increase the quality of life of neuropsychiatric veterans.